2015
DOI: 10.1186/s13058-015-0586-z
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the technologies and review of the genomic landscape of ductal carcinoma in situ of the breast

Abstract: Ductal carcinoma in situ is a biologically diverse entity. Whereas some lesions are cured by local surgical excision, others recur as in situ disease or progress to invasive carcinoma with subsequent potential for metastatic spread. Reliable prognostic biomarkers are therefore desirable for appropriate clinical management but remain elusive. In common with invasive breast cancer, ductal carcinoma in situ exhibits many genomic changes, predominantly copy number alterations. Although studies have revealed the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
(145 reference statements)
1
3
0
Order By: Relevance
“…Studies of conventional DCIS have demonstrated largely similar mutational and copy number profiles between the in situ and invasive components, albeit with increased numbers of copy number alterations in invasive cancer, and our results in metaplastic carcinomas are consistent with this [61][62][63][64][65]. As in conventional DCIS [62,63,65,66], we show that PIK3CA alterations are early events in metaplastic carcinoma, with mutations in this and other growthpromoting PI-3 kinase/Ras-Map kinase pathway genes being present in clonal frequencies of associated DCIS and paired invasive tumors.…”
Section: Discussionsupporting
confidence: 88%
“…Studies of conventional DCIS have demonstrated largely similar mutational and copy number profiles between the in situ and invasive components, albeit with increased numbers of copy number alterations in invasive cancer, and our results in metaplastic carcinomas are consistent with this [61][62][63][64][65]. As in conventional DCIS [62,63,65,66], we show that PIK3CA alterations are early events in metaplastic carcinoma, with mutations in this and other growthpromoting PI-3 kinase/Ras-Map kinase pathway genes being present in clonal frequencies of associated DCIS and paired invasive tumors.…”
Section: Discussionsupporting
confidence: 88%
“…[25][26][27][28][29]. We found that in HG DCIS copy number changes in our candidate genes were not differentially distributed in PD and MD lesions ( Table 2), indicating that in this subgroup our oligo-gene signature may not be useful.…”
Section: Positivementioning
confidence: 81%
“…Genomic DNA biomarkers report genome-level changes using a variety of methods, including genome sequencing, qPCR and digital PCR 148 to accurately report SNPs, CNVs, genomic rearrangements and rare genetic sequences that functionally underpin the pathophysiology of disease 149 . This approach is most frequently used in oncology.…”
Section: Evs and Dna Biomarkersmentioning
confidence: 99%